Finding a rhythm within - Jan-Albert van den Berg (Acta Theologica)
Intimate, a-rhythm autobiographical experiences, originating from my own life text, serve as initial rhetorical spaces in which possible melodies of persuasion can be heard. In this regard, polyphony serves as the central metaphor in this article. Initially, this musical metaphor acquired theological meaning in the Christological reflection of the well-known German theologian Dietrich Bonhoeffer. Four idiomatic soundtracks, namely tonedeaf, rhythm, polyphonic narratives, and dance determine the structure of the article. Although each of these soundtracks represents a unique story, together they create a harmonious melody, as in the central metaphor of polyphony. In this newly composed polyphonous melody, my own voice is audibly and rhetorically integrated with the resonant tone of development within practical theology and pastoral care. The new contribution offered by this article is found in the autobiographical pastoral reflections of persuasion on the newly composed polyphonic melody, creating a harmonious rhythm within identity and praxis.